Smart Heritage for Urban Sustainability: A Review of Current Definitions and Future Developments - Heng Song; Gehan Selim (Alanya Hamdullah Emin Paşa Üniversitesi, 2022)
Smart heritage is still novel in heritage discourse, with a few relevant review articles. In this regard, a specific interpretation of smart architectural heritage and a framework for instructing its development is lacking. This article reviews the literature on smart heritage in sustainable development to fill the knowledge gap. As a methodology for this study, the integrative review approach and thematic analysis are adopted to review references located at the crossroads of historic, smart, and sustainable disciplines. The review and interpretation draw on literature from relevant fields to understand implementations, current states, and support to interpret smart heritage. Review outcomes indicate that smart heritage is becoming dynamic as technologies are increasingly applied to more detailed heritage branches. This article lists the factors that heritage should possess to be defined as smart, and it provides a framework that might be followed to achieve the aims of this discourse by stating that smart heritage discussions are relevant to smart cities, as they may have a mutual effect and interact to promote each other.